Cd248a and Cd248b in zebrafish participate in innate immune responses - Li, Xianpeng; Guo, Ruitong; Yang, Shuaiqi; Zhang, Xiangmin; Yin, Xiu; Teng, Lei; Zhang, Shicui; Ji, Guangdong; Li, Hongyan (Frontiers in Immunology, 2022)
CD248, also known as endosialin or tumor endothelial marker 1, is a type I single transmembrane glycoprotein. CD248 has been demonstrated to be upregulated in cancers, tumors and many fibrotic diseases in human and mice, such as liver damage, pulmonary fibrosis, renal fibrosis, arthritis and tumor neovascularization. However, no definite CD248 orthologs in fish have been documented so far. In this study, we report the identification of cd248a and cd248b in the zebrafish. Both the phylogenetic analysis and the conserved synteny strongly suggested that zebrafish cd248a and cd248b are orthologs of the human CD248. Both cd248a and cd248b exhibited similar and dynamic expression pattern in early development, both genes had weak maternal expression, the zygotic transcripts were first seen in anterior somites and head mesenchyme, then shifted to eyes and head mesenchyme, later expanded to branchial arches, and gradually declined with development. The expression profiles of cd248a and cd248b were upregulated upon LPS (Lipopolysaccharide) challenge. Both Cd248a protein and Cd248b protein were localized on the cell membrane and cytoplasm, and overexpression of cd248a and cd248b induced the expression of pro-inflammatory cytokines, in vitro and in vivo. Moreover, deficiency of cd248a or cd248b both downregulated the expression of pro-inflammatory cytokines and upregulated anti-inflammatory cytokine. Additionally, loss of cd248a or cd248b both downregulated the expression of pro-inflammatory cytokines after LPS treatment. Taken together, these results indicated that cd248a and cd248b in zebrafish were involved in immune response and would provide further information to understand functions of Cd248 protein in innate immunity of fish.